The Effectiveness of Arabic Language Learning in Optimizing Students' Memorization Abilities at the Tahfidzh Kawan M77 House - Sarah Riza M Sarah; Robin Sirait; Muhammad Najari; Surya Bakti (The Islamic Education and Multiculturalism Foundation, 2026)
Abstrak Penelitian ini menganalisis efektivitas integrasi pembelajaran bahasa Arab dalam mengoptimalkan keterampilan hafalan Al-Qur'an di Rumah Tahfizh Kawan M77. Kesenjangan penelitian ini didasarkan pada fenomena umum di lembaga pendidikan nonformal yang sering memisahkan kurikulum bahasa Arab dari kurikulum tahfizh, sehingga siswa cenderung menghafal teks secara mekanis tanpa pemahaman linguistik yang mumpuni. Dengan menggunakan metode deskriptif kualitatif melalui observasi peserta, dokumentasi, dan wawancara mendalam, penelitian ini mengumpulkan kontribusi komponen Nahwu, Sharaf, dan Qiraatul Kutub dalam meningkatkan daya ingat siswa. Implikasi teoretis dari temuan ini memperkuat paradigma kognitivisme dan konstruktivisme dalam pendidikan Islam, yang menegaskan bahwa memahami semantik sumber bahasa memungkinkan pemrosesan mendalam, yang secara linier meningkatkan retensi memori jangka panjang. Sebagai kontribusi praktis untuk pedagogi bahasa Arab, penelitian ini menawarkan model integrasi kurikulum yang menggabungkan penguasaan aturan bahasa dengan hafalan yang dipercepat. Hasil penelitian menegaskan bahwa keberhasilan program tahfizh tidak hanya bergantung pada intensitas kontribusi, tetapi pada sinergi antara kompetensi guru dalam menjelaskan makna linguistik, motivasi intrinsik siswa, dan terciptanya lingkungan bahasa yang mendukung ekosistem pembelajaran di lembaga pendidikan Islam. Kata kunci: Integrasi pembelajaran bahasa Arab, Menghafal Al-Qur'an (tahfizh, Konstruktivisme kognitif, pemahaman linguistik. Abstract This study analyzes the effectiveness of integrated Arabic language learning in optimizing Quran memorization skills at Rumah Tahfizh Kawan M77. This research gap stems from a common phenomenon in non-formal educational institutions, where the Arabic language curriculum is often separated from the tahfizh program, resulting in students mechanically memorizing texts without adequate linguistic understanding. Using a qualitative descriptive approach through participant observation, documentation, and in-depth interviews, this study evaluates the contribution of Nahwu, Sharaf, and Qiraatul Kutub in supporting students' memory retention. The theoretical implications of the findings reinforce the cognitivist and constructivist paradigms in Islamic education, emphasizing that understanding the semantics of the source language enables in-depth information processing, which in turn enhances long-term memory retention. In terms of practical contributions to Arabic language pedagogy, this study proposes an integrated curriculum model that combines mastery of linguistic rules with accelerated memorization. The results highlight that the success of a tahfizh program depends not only on the intensity of memorization practice but also on the synergy between teacher competence in explaining linguistic meanings, students' intrinsic motivation, and the creation of a language-rich environment that supports a sustainable learning ecosystem in Islamic educational institutions. Keywords: Integration of Arabic Language Learning, Memorizing the Qur'an (Tahfizh), Cognitive Constructivism, Linguistic Understanding.